1989
DOI: 10.1177/019459988910100310
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Stimulated Increases in Cochlear Blood Flow: II. Evidence of Neural Mediation

Abstract: In a companion paper, we reported that electrical stimulation increased cochlear blood flow (CBF). This response was found to be an increasing function of current intensity and was frequency-selective, with the best response at approximately 500 Hz continuous sinusoidal current. The present investigation seeks to discover the mechanism of this effect. Direct measurement of cochlear temperature during electrical stimulation revealed no evidence of local heating. Autonomic neuronal activation is not likely, as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In preliminary studies we confirmed the lack of effect of systemically administered cholinergic (nicotinic and muscarinic) antagonists on the ES-evoked CBF increase as shown previously in the guinea-pig (Sillman et al 1989b). With regard to the general principle of a cholinergic receptor mediation, we note that a cholinergic response usually exhibits a fast on-off function due to the quick release of acetylcholine in the nerve endings and fast (200-300 ms) breakdown of the transmitter by acetylcholinesterase (Colquhoun, 1979).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In preliminary studies we confirmed the lack of effect of systemically administered cholinergic (nicotinic and muscarinic) antagonists on the ES-evoked CBF increase as shown previously in the guinea-pig (Sillman et al 1989b). With regard to the general principle of a cholinergic receptor mediation, we note that a cholinergic response usually exhibits a fast on-off function due to the quick release of acetylcholine in the nerve endings and fast (200-300 ms) breakdown of the transmitter by acetylcholinesterase (Colquhoun, 1979).…”
Section: Discussionsupporting
confidence: 89%
“…The roles of evoked LaRouere, Masta, Miller & Nuttall, 1989a; Sillman, Masta, metabolic activity, oxygen-free radical formation, and LaRouere, Nuttall & Miller, 1989b). Increased CBF, heat in this response were examined in previous studies induced by ES, has also been reported in humans (Miller, (Sillman et al 1989b). No evidence was obtained to support All correspondence to A. L. Nuttall.…”
Section: Previous Studies Have Shown That Electrical Stimulation (Es)mentioning
confidence: 96%
See 1 more Smart Citation
“…The normal function of the cochlea relies very much on both the intracellular and extracellular milieu, particularly the cochlear microcirculation [12]. The cochlea receives its blood supply mainly from the labyrinthine artery without shunting from collateral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Autoregulatory capabilities of the cochlear blood fl ow occur through the control of inner ear vasculature [Ren et al, 1994], sympathetic input to the cochlea [Carrasco et al, 1990;Laurikainen et al, 1993;Ren et al, 1993a, b] and the infl uence of various circulating vasoactive hormones and transmitters [Wright et al, 1985;Short et al, 1985;Miller et al, 1986;Sillman et al, 1989;Quirk et al, 1988;Ohlsen et al, 1991]. The aged ear has less capacity to maintain stable blood fl ow and thus may be more vulnerable to stress factors that affect cochlear function [Nakashima et al, 1995;Suzuki et al, 1998], starting with defi cits in OHCs.…”
Section: Teoae and Dpoae Amplitudesmentioning
confidence: 99%